2021
DOI: 10.1177/09636897211052300
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Methamphetamine Sensitization by Partially Lesioning Dopaminergic Terminals with 6-Hydroxydopamine in Nucleus Accumbens

Abstract: Amphetamine-type stimulants have become important and popular abused drugs worldwide. Methamphetamine (Meth) sensitization, characterized by a progressive increase in behavioral responses after repeated administration, has been reported in rodents and patients. This behavioral effect has been used as a laboratory model to study drug addiction and schizophrenia. The mesolimbic dopaminergic pathway plays a significant role in the development of Meth behavioral sensitization. Previous studies have reported that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In addition, we confirmed that 25D-NBOMe increased the expression level of TH, an enzyme that catalyzes the synthesis of catecholamines, including DA. Since psychostimulants, including methamphetamine, increase DA release in the NAc, it can be considered that repeated administration of psychostimulants increases TH expression in the NAc. , Taken together, these results demonstrate that 25D-NBOMe exhibits rewarding and reinforcing effects by inducing dopaminergic protein changes, similar to other addictive drugs.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, we confirmed that 25D-NBOMe increased the expression level of TH, an enzyme that catalyzes the synthesis of catecholamines, including DA. Since psychostimulants, including methamphetamine, increase DA release in the NAc, it can be considered that repeated administration of psychostimulants increases TH expression in the NAc. , Taken together, these results demonstrate that 25D-NBOMe exhibits rewarding and reinforcing effects by inducing dopaminergic protein changes, similar to other addictive drugs.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast to PD animals, in manic‐like SD rats, we observed an increase of TH expression through the reduction of miR‐330‐5p in the prefrontal cortex. A previous study also showed an increase of TH expression in the nucleus accumbens of methamphetamine‐treated mice, which are considered a model for mania, schizophrenia, and addiction, showing enhanced synaptic dopamine levels 50 . Interestingly, injection of dopaminergic toxin 6‐hydroxydopamine (6‐OHDA) antagonized the increase of TH in methamphetamine‐treated mice 50–52 .…”
Section: Discussionmentioning
confidence: 89%
“…A previous study also showed an increase of TH expression in the nucleus accumbens of methamphetamine‐treated mice, which are considered a model for mania, schizophrenia, and addiction, showing enhanced synaptic dopamine levels. 50 Interestingly, injection of dopaminergic toxin 6‐hydroxydopamine (6‐OHDA) antagonized the increase of TH in methamphetamine‐treated mice. 50 , 51 , 52 6‐OHDA is also a neurotoxin used to produce Parkinsonism rodent models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primer sequences for the OPG were as follows: forward, 5′-AGC AGG AGT GCA ACC GCA CC-3′ and reverse, 5′-TTC CAG CTT GCA CCA CGC CG-3′ [ 23 ]. The primer sequences for glyceraldehyde-3-phosphate dehydrogenase were as follows: forward, 5′-CAT CAC TGC CAC CA GAA GAC TG-3′ and reverse, 5′-ATG CCA GTG AGC TTC CCG TTC AG-3′ [ 24 ].…”
Section: Methodsmentioning
confidence: 99%